Effect of Tamarindus indica L. fruit pulp and seed extracts on experimental ulcerative colitis in rats - Mohsen Minaiyan; Sepehr Abolhasani; Setareh Sima; Afsaneh Yegdaneh (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Tamarindus indica L. which has anti-inflammatory, radical scavenging, and ulcer healing effects can be useful for the alleviation of inflammatory bowel disease (IBD). Therefore, the effects of T. indica fruit pulp (TIPE) and seed extracts (TISE) were investigated on experimental colitis. Experimental approach: TIPE and TISE (125, 250, and 500 mg/kg) were made by maceration (ethanol/water: 80/30) and administered to male Wistar rats with acetic acid-induced colitis. Prednisolone (4 mg/kg) and mesalazine (100 mg/kg) were used as reference drugs. The colon tissues were examined for macroscopic and pathologic parameters and myeloperoxidase (MPO) and malondialdehyde (MDA) values. Findings/Results: The total phenols were 45.7 ± 1.1 and 453.0 ± 3.3 mg/g in terms of gallic acid for TIPE and TISE, respectively. Both of the extracts significantly improved most of the investigated parameters including body weight loss, the weight of colons, indices of ulcers, and total colitis. MPO activity and MDA in the treatment groups (except for TIPE at 125 mg/Kg) significantly decreased compared to the control. Conclusion and implications: Both TIPE and TISE were effective in the treatment of colitis however it seems that the effective ingredients were more concentrated in seeds rather than pulp extract so the highest dose of seed extract had a competitive effect with reference drugs. More studies are needed to introduce T. indica as a suitable complementary medicine or food for patients with IBD.